RECALL prompting hierarchy improves responsiveness for autistic children and children with language delay: a single-case design study - Bosley, Rebekah; Loveall, Susan J.; Kellum, Karen Kate; Hawthorne, Kara (Frontiers in Psychology, 2024)
The purpose of the current study was to expand upon previous research on RECALL (Whalon et al., 2015), a dialogic reading intervention modified for autistic children aimed at increasing engagement. Children ages 3-6 years (n = 6) with language delays with or without co-occurring autism were tested using a multiple baseline across participants design. During baseline, the interventionist used dialogic reading and asked questions after every page. During intervention, the interventionist used RECALL, including a least to most prompting hierarchy with visual prompt cards. Children were more responsive and produced more meaningful correct responses during the intervention. Response type (linguistic vs. non-linguistic) also changed from baseline to intervention, though the pattern varied across participants. Intervention was not associated with increased responsiveness to adult bids for attention or pauses designed to encourage the child to initiate an interaction, though a few children showed changes in these responses over time.